MECHANISM OF WATER ADVANCING IN PLANT XYLEM CAPILLARIES - Iosif Anshelevich Kipnis; Yury Mikhailovich Vernigorov (Advanced Engineering Research)
The mechanism of water rise in the xylem which allows the description of the water distribution in plants taking into account their anatomy, architectural form, and the influencing external factors is considered. The assumption is made that the primary mechanism for the water promotion in plants is a capillary rise. The major driving force to lift water to the top of the plant is the superficial tension in the capillary menisci. It has been established that the condition for lifting water in plants is, firstly, the presence of the water horizontal movement. Secondly, the total cross-section area of capillaries should increase from the butt-end to the top. It is shown that the plant height is determined by the number of its lateral branches, as well as the presence of cross perforated plates in the xylem vessels. The mechanism of the self-oscillating mode of the plant transpiration at small time intervals is explained.